Freedom to Learn – Independent Campus (MBKM) Curriculum Management at the Indonesian Language Tadris Degree Program (TBI) of Islamic Religious Higher Education Institutions (PTKI) - Isnaniah, Siti; Kurniawan, Kurniawan (Jurnal Pendidikan Islam, 2022)
Purpose – This study aims to explain the management of the MBKM curriculum in the TBI Degree Program at PTKI and the implementation of forms of collaboration with partners who support the MBKM program’s implementation. The data was gathered from the TBI Degree Program at UIN Raden Mas Said (RMS) Surakarta. Design/methods/approach – This study employs a qualitative explanatory method. Documents, informants, and events serve as data sources. Data collection methods included content/document analysis, in-depth interviews, and observation. The data analysis technique employs an interactive model. The triangulation technique is used in the data validity technique. Findings – The results show that the MBKM Degree Program curriculum design at UIN RMS Surakarta has incorporated 21st-century skills. Several courses will require digital skills, such as Digital Literacy, Monetization of Digital Products, and Development of Indonesian Language Learning Media starting in 2019. TBI’s Degree Program, Starting in 2019 in support of MBKM, has also implemented collaboration with various partners, including the Industrial World Business World (DUDI). Research implications/limitations – This research contributes to understanding the importance of implementing MBKM in the TBI Degree Program at PTKI, with the data source being the TBI Degree Program Faculty of Adab and Language at UIN Raden Mas Said Surakarta. It can be used as a model for other TBI Degree Programs at PTKI that have not implemented MBKM much. in designing the curriculum. Practical implications – This research can provide practical training in the Indonesian Tadris curriculum and a curriculum review for MBKM design.